Mental Health Screening and Education for Adolescents at Jenderal Achmad Yani University - Bunga Tiara Carolin; Sophia; Nanik Cahyati; Lina Haryani; Noviyanti; Yeni Rosyeni; Ranti Widayanti; Mega Dewi Lestari (International Journal of Community Services, 2025)
The Indonesia National Adolescent Mental Health Survey (I-NAMHS) shows data that 1 in 3 teenagers aged 10-17 years in Indonesia have had mental health problems in the last 12 months. The highest prevalence occurs in the age group 15-24 years and female gender. There are many factors that influence the mental and emotional state of teenagers, namely the family environment, peers, school environment, community environment and social media. For teenagers, peer support for emotional support such as empathy, care and attention is very important because it can make them feel loved and increase self-esteem. One way to improve mental health in teenagers is by increasing teenagers' knowledge about mental health Keywords: Mental Health, Screening, Education, Adolescent